A Statewide Analysis of the Impact of Restitution and Fees on Juvenile Recidivism in Florida Across Race & Ethnicity - Piquero, Alex R. (Youth violence and juvenile justice, 2023)
Whether the imposition of monetary sanctions is related to juvenile recidivism is explored overall and across race and ethnicity. Leveraging a statewide sample, logistic regression was used to predict fees and restitution assignment based on youth/case characteristics, hierarchical linear and logistic random-effects regression examined the association between neighborhood characteristics with fees and restitution, and propensity score matching examined whether fees and/or restitution are related to reoffending. No race/ethnic differences were found in the proportion of youth receiving court fees, yet when fees were administered both Black and Hispanic youth received higher fees. Neighborhood characteristics have minimal impact on whether (or the amounts) monetary sanctions were assigned. Post-matching, fees increased recidivism, as did being Black or Hispanic. Interactions between race/ethnicity and both fees and restitution showed Black youth with restitution had a higher recidivism likelihood. Monetary sanctions imposed on youth involved in the juvenile justice system has a potential deleterious impact on recidivism.